Preparation and Identification of Some New Derivatives of 4-Bromoaniline - AL-Masoudi, N. A.; AL-Redha, N. A. A.; Jihad, R. S. (Al-Qadisiyah Journal of Pure Science, 2018)
This paper is ensured synthesis of some heterocycle derivatives of 4-bromoaniline compound that likely they are to be effective vital task was diagnosed spectrally by spectrum of IR and the spectrum of NMR (1H & 13C), as well as using C.H.N. analysis and study of some physical properties. Derivatives (1-5) was prepared as benzothiazole derivatives, (1) derivative was prepared by reacting 4-bromoaniline with ammonium thiocyanate existence Br2 as a catalyst and glacial acetic acid as medium of reaction and attended (2) & (3) derivatives by smelting of maleic and phthalic anhydride with (1) derivative, respectively, also attended the (4) derivative by reactance (1) derivative with potassium thiocyanate ,using the technique of microwave, (5) derivative prepared from (1) by using microwave technique and follow the Suzuki reaction and presence of 4-cyanophenyl boronic acid,mwhile (7) & (8) derivatives prepared as thiazolidine derivatives from (6) derivative that was prepared by reactance 4-bromoaniline with chloroacetylchloride, by it reacting with potassium and ammonium thiocyanate, respectively.